1979
DOI: 10.2172/5584354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resource impact factors versus social cost estimates in determining building energy performance standard levels

Abstract: SUMMARYThe development of standards governing the designed energy consumption of buildings has been sought by Congress to increase energy conservation. In determining what degree of energy conservation is desirable, efficiency and equity issues must be considered. Development of a performance standard that constrains design energy consumption to an economically efficient level requires identification of the least cost means of producing the desired building space conditioning characteristics. Accurate valuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…While there are minor damages to water and land resources as a result of natural gas production processes, most of the emissions affect air quality. Table 16 shows emissions estimates per million Btu of gas input to each (a) See appendix of Nieves et al (1979) for an annotated list of the studies reviewed. .70 x 10-4 8.5 x 10-5 4.9 x 10-4 1.84 x 10-2 NO x 5.3 x 10-3 3.76 x 10-3 5.68 x 10-4 2.06 x 10-1 1.39 x 10-2 2.44 x 10-2 2.44 x 10-2 4.85 x 10-2 SOx 1.9x1O-5 2.84 x 10-6 1.02 x 10-3 5.52 x 10-Hydrocarbons 5.54 x 10-1 1.26 x 10-3 1.89 x 10-4 1.39 x 10-3 7.78 x 10-CO 1.26x10-5 1.89 x 10-6 8.46 x 10-3 1.94 x 10-Aldehydes 3.14 x 10-4 4.72 x 10-5 2.26 x 10-4 9.68 x 10- Source: Meres (a) Estimates are unlikely to be off by more than fifty percent.…”
Section: Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are minor damages to water and land resources as a result of natural gas production processes, most of the emissions affect air quality. Table 16 shows emissions estimates per million Btu of gas input to each (a) See appendix of Nieves et al (1979) for an annotated list of the studies reviewed. .70 x 10-4 8.5 x 10-5 4.9 x 10-4 1.84 x 10-2 NO x 5.3 x 10-3 3.76 x 10-3 5.68 x 10-4 2.06 x 10-1 1.39 x 10-2 2.44 x 10-2 2.44 x 10-2 4.85 x 10-2 SOx 1.9x1O-5 2.84 x 10-6 1.02 x 10-3 5.52 x 10-Hydrocarbons 5.54 x 10-1 1.26 x 10-3 1.89 x 10-4 1.39 x 10-3 7.78 x 10-CO 1.26x10-5 1.89 x 10-6 8.46 x 10-3 1.94 x 10-Aldehydes 3.14 x 10-4 4.72 x 10-5 2.26 x 10-4 9.68 x 10- Source: Meres (a) Estimates are unlikely to be off by more than fifty percent.…”
Section: Emissionsmentioning
confidence: 99%
“…In a recent examination of fuel markets, prices and nonmarket costs (Nieves et al 1979), evidence was found of market failure resulting in fuel prices that do not reflect the total social costs of the resources consumed. The pricing of energy at less than its marginal social cost leads to choices of building energy systems which result in higher annual levels of fuel consumption than would occur if all of the relevant resources were accurately or proportionally inaccurately priced.…”
Section: Introductionmentioning
confidence: 99%